Parallel Worlds. - Berben, Jos; Van Knippenberg, Tony; CIAP vzw, Hasselt (Hasselt : CIAP Actuele Kunst vzw, 2012)
Berkvens, Elise ; Cielen, Fia ; Coolen, Caroline ; Geenen, Pieter ; Geurts, Frederic ; Hulsmans, Peter ; Philips, Karl ; Roncada, Arno ; Van Dingenen, Filip ; Vanmechelen, Koen
Parallel Worlds, CIAP Actuele Kunst, Hasselt, 2 juni tot 30 september 2012
boek